Municipal officials' propensity toward active transportation: A rural-urban comparison. (March 2019) - Blanchette, Sébastien; Lemoyne, Jean; Rivard, Marie-Claude; Trudeau, François
Abstract: Introduction: Built environments can influence physical activity habits. Their features vary according to population size and density. In developed countries, rural populations often display higher rates of obesity and lower levels of physical activity compared with urban populations. This study aims to 1) assess municipal officials' propensity to improve their community's environment to render it conducive to active transportation (AT), and 2) assess whether the level of propensity varies between municipal officials from rural and urban communities. Methods: In 2015, 412 of an invited 1661 municipal officials in Quebec (Canada) completed an online survey. Among them, 57% served a rural community. The Theory of Planned Behavior served as the theoretical framework for measuring participants' propensity to implement policies conducive to citizens' AT. Structural Equation Modeling was used to analyze relations between variables. Tests of invariance compared rural and urban municipal officials. Results: Antecedent actions related to AT and perceived control were the two key factors that predicted officials' intentions to take action toward AT. Attitudes also predicted intentions toward AT to a lesser extent. The contribution from subjective norms was not significant. In summary, the model accounted for 60% of explained variance (R 2 ) in intentions. The model applied to both groups, but urban officials reported more antecedent actions and a higher perceived control than rural officials. Conclusions: Improving municipal officials' competencies and support from public health networks along with a greater investment of time and resources could increase their perceived control and involvement in AT-related policies, especially in rural communities. Highlights: Built environment and policies can influence physical activity and active transportation. Policies on built environment and active transport occur largely at the municipal level. Antecedent actions and perceived control predicted officials' intentions to take action. Rural (versus urban) officials reported fewer actions and lower perceived control. More support and resources could boost municipal incentives on active transportation.